2015
DOI: 10.1039/c5sm01382h
|View full text |Cite
|
Sign up to set email alerts
|

Celebrating Soft Matter's 10th Anniversary: Cell division: a source of active stress in cellular monolayers

Abstract: We introduce the notion of cell division-induced activity and show that the cell division generates extensile forces and drives dynamical patterns in cell assemblies. Extending the hydrodynamic models of lyotropic active nematics we describe turbulent-like velocity fields that are generated by the cell division in a confluent monolayer of cells. We show that the experimentally measured flow field of dividing Madin-Darby Canine Kidney (MDCK) cells is reproduced by our modeling approach. Division-induced activit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 105 publications
(117 citation statements)
references
References 60 publications
3
108
2
Order By: Relevance
“…To study the transition to low-Reynolds-number meso-scale turbulence, we computationally solve the continuum equations of active nematics in micro-channels, which have successfully reproduced the patterns of bacterial ordering in bulk5 and in confinement21, the flow structure and correlation lengths of microtuble bundles101122 and the flow patterns of dividing cells823 (see Methods for the details of the model). Through this continuum description, the transition to turbulence occurs by increasing the amount of local energy injection (activity) in the living fluids.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To study the transition to low-Reynolds-number meso-scale turbulence, we computationally solve the continuum equations of active nematics in micro-channels, which have successfully reproduced the patterns of bacterial ordering in bulk5 and in confinement21, the flow structure and correlation lengths of microtuble bundles101122 and the flow patterns of dividing cells823 (see Methods for the details of the model). Through this continuum description, the transition to turbulence occurs by increasing the amount of local energy injection (activity) in the living fluids.…”
Section: Resultsmentioning
confidence: 99%
“…This formulation has been extensively applied to biological systems including bacterial suspensions21, microtuble/motor protein mixtures102242 and cellular monolayers843. The total density ρ and the velocity field u of the active matter obey the incompressible Navier–Stokes equations…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Models of this kind reproduce a variety of non-equilibrium flows such as stable arrays of vortices or chaotic flows, together with diverse stationary and non-stationary patterns of nematic ordering and topological defects [39,40,33,29,28,41,42,43]. On a phenomenological level, these are successful in modelling the collective dynamics in biological systems in cases such as microtubule/motor-protein mixtures [44,33,40], cellular monolayers [45,46,47,35], or bacteria [48]. In addition to the bulk dynamics, the interaction with walls or obstacles of different shape can add further complexity.…”
Section: Modelmentioning
confidence: 99%
“…ξ = 0.7 leads to alignment of the director to an external flow in a passive nematic. Parameter fitting of the continuum equations to physical active systems remains a topic of research; therefore, we consider a generic parameter set that has been shown to reproduce the flow vortex-lattice generated by a dense assembly of endothelial cells [59,60], and the flow fields of dividing Madin-Darby Canine Kidney cells [47]. Independent samples for parameter sets are obtained by varying the initial condition randomly.…”
Section: Simulation Setupmentioning
confidence: 99%